The teaching of grammar among the commentators of classical didactic texts (metan manuals) - .belhadj, amal (El Omda in Linguistics and Discourse Analysis, 2025)
This study aims to clarify the work of commentators of classical didactic grammatical texts, who made considerable efforts to simplify the raw scientific material found in linguistic and grammatical matn, which served as a foundation for solving linguistic problems and teaching grammar to students and beginners. Early grammatical works, such as Sibawayh’s Book and others, required clarification, as they compiled linguistic material drawn from poetic and prose corpora. This research seeks to highlight the pedagogical dimension in their works and their methods of presenting grammatical material. Their activity can be considered part of modern grammar didactics, since their commentaries on grammatical and linguistic texts are characterized by facilitation, clarification, detailed explanation, and simplification of scientific content. In doing so, they achieved a high level of organization and elucidation of grammatical material, including syntactic analysis and the comprehensive treatment of meanings and interpretations. As a result, both the researcher and the learner find what they are seeking, achieving their objectives while moving through the pages and chapters of these commentaries, and experiencing the pleasure of practice, analysis, and comprehension.